Haptic Guidance System for Teleoperation Based on Trajectory Similarity - Hikaru Nagano; Tomoki Nishino; Yuichi Tazaki; Yasuyoshi Yokokohji (Robotics)
Teleoperation technology enables remote control of machines, but often requires complex manoeuvres that pose significant challenges for operators. To mitigate these challenges, assistive systems have been developed to support teleoperation. This study presents a teleoperation guidance system that provides assistive force feedback to help operators align more accurately with desired trajectories. Two key issues remain: (1) the lack of a flexible, real-time approach to defining desired trajectories and calculating assistive forces, and (2) uncertainty about the effects of forward motion assistance within the assistive forces. To address these issues, we propose a novel approach that captures the posture trajectory of the local control interface, statistically generates a reference trajectory, and incorporates forward motion as an adjustable parameter. In Experiment 1, which involved simulating an object transfer task, the proposed method significantly reduced the operator’s workload compared to conventional techniques, especially in dynamic target scenarios. Experiment 2, which involved more complex paths, showed that assistive forces with forward assistance significantly improved manoeuvring performance.